Methods for Measuring Potential Bankruptcy of Sharia Banking - Ridwan, Mukminati; Pagalung, Gagaring; Kara, Muslimin (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2022)
This study aims to examine the methods that can be used to measure bankruptcy in sharia banking. This study is also to examine the potential for bankruptcy which is most effectively used. The method used is descriptive qualitative method with a literature approach. The results showed that of the six bank measurement methods, all of them could not be used to measure bankruptcy in Sharia banking without being modified first. This is because all methods have constituent elements based on interest and taxes. All methods can be used when eliminating the elements of interest and taxes. However, based on the research, it was found that the most widely used method to measure bankruptcy is the Altman Z-Score model, but the Springate S-score is the most effective in detecting the bankruptcy of Sharia banking in Indonesia.